Protective effects of Angelica sinensis polysaccharide on chemotherapy-injured rats with premature ovarian insufficiency and its impact on gut microbiota - Wu, Maoyuan; Shu, Haixia; Wang, Min; Xu, Yan; Zhang, Yunhan; Jiang, Xiaoling; Zhang, Lixia; Chen, Xuemei; He, Lianli (Frontiers in Pharmacology, 2025)
ObjectiveThis study aimed to investigate the therapeutic effects and action mechanisms of Angelica sinensis polysaccharides (ASP) on a chemotherapy-induced premature ovarian insufficiency (POI) rat model along with screening for the optimal therapeutic dose.MethodsSprague–Dawley female rats were used to establish a POI rat model via intraperitoneal injection of cyclophosphamide and busulfan. The rats were treated with ASP at doses of 80, 160, and 320 mg/kg/d for 21 d. The ovarian histomorphology and follicular development were examined by hematoxylin and eosin staining, and the serum levels of follicle-stimulating hormone (FSH), luteinizing hormone (LH), estradiol (E2), anti-Müllerian hormone (AMH), and inflammatory cytokines (IL-6, IL-1β, and TNF-α) were measured. The ovarian oxidative stress was assessed via malondialdehyde (MDA), superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and reactive oxygen species (ROS) levels. The composition of the gut microbiota was analyzed by 16S rDNA sequencing, and the associations between differential microbiota and ovarian indicators were assessed using Spearman correlation analysis.ResultsASP treatment improved sex hormone secretion in the chemotherapy-induced POI rats, in addition to increased E2 and AMH levels, decreased FSH and LH levels, improved ovarian tissue structure, and increased follicle growth at all stages. ASP treatment also improved the serum inflammatory levels in POI rats by reducing the IL-6, IL-1β, and TNF-α levels; it decreased oxidative stress levels in the ovarian tissue, inhibited ROS and MDA activities, and increased SOD and GSH-Px activities. The gut microbiota differential analysis showed that chemotherapy-induced POI rats exhibited dysbiosis of the gut microbiota. After ASP treatment, the α and β diversities of the gut microbiota changed, thereby increasing the relative abundance of beneficial bacteria and decreasing the relative abundance of harmful bacteria. Spearman’s correlation analysis was performed between the main differential microbiota as well as serum sex hormone, proinflammatory cytokine, and ovarian tissue oxidative stress levels; accordingly, the results showed that some beneficial bacteria were positively correlated with E2, AMH, SOD, and GSH-Px levels while being negatively correlated with FSH, LH, MDA, IL-6, IL-1β, and TNF-α levels.ConclusionASP ameliorates chemotherapy-induced POI in rats by improving the serum hormone levels, promoting follicular development, as well as suppressing inflammation and oxidative stress, with medium and high treatment doses showing significant efficacies. Furthermore, ASP reshapes the gut microbiome; the altered gut microbiota are strongly correlated with ovarian function indicators, suggesting that they may serve as a new therapeutic approach for POI.